2011
DOI: 10.1167/iovs.10-6054
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Imaging of Human Foveal Capillary Network Using Dual-Conjugate Adaptive Optics

Abstract: The authors have demonstrated a technique for noninvasive imaging and semiautomated detection and analysis of foveal capillaries. In comparison with other studies, their method yielded lower capillary densities than histology but similar results to the current clinical gold standard, fluorescein angiography. The increased field of view of the DCAO instrument opens up new possibilities for high-resolution noninvasive clinical imaging of foveal capillaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 18 publications
4
44
0
1
Order By: Relevance
“…These findings are consistent with previous studies using other techniques. For example, Tan and associates observed a similar result using a confocal microscope technique,2 while others have performed detailed investigations of vessel density using adaptive optics scanning laser ophthalmoscopy and dual-conjugate adaptive optics 3 4. When compared with these results, our vessel density for each layer was lower.…”
Section: Resultsmentioning
confidence: 55%
“…These findings are consistent with previous studies using other techniques. For example, Tan and associates observed a similar result using a confocal microscope technique,2 while others have performed detailed investigations of vessel density using adaptive optics scanning laser ophthalmoscopy and dual-conjugate adaptive optics 3 4. When compared with these results, our vessel density for each layer was lower.…”
Section: Resultsmentioning
confidence: 55%
“…Also, there is no current standard in measurement of capillary density, and previous quantification methods using histopathology, adaptive optics scanning laser ophthalmoscopy, and OCT have some variation in measured values, as well as representation. [25][26][27][28][29][30][31][32] However, assuming capillary density is statistically similar in both eyes of a single patient, we believe the decrease in capillary density is a true finding in eyes with radiation maculopathy. We believe our technique using a third party photo-editing software (Adobe Photoshop or ImageJ) can reliably quantify capillary density.…”
Section: Discussionmentioning
confidence: 83%
“…After controlling for confounding factors, we found that parafoveal vessel density and FAZ circularity index were independently related to mGCIPL thinning in the present study (table 3). Similarly, previous studies have suggested that changes in the FAZ circularity index13 and parafoveal vessel density12 are more reliably correlated with microcirculation impairment in DR. FAZ size shows high variability in healthy eyes, and it is affected by individual differences in ocular magnification such as variation in axial length 21. To our knowledge, this is the first study to report the relationship between changes of OCTA-derived microvascular parameters and mGCIPL thickness in patients with T2DM.…”
Section: Discussionmentioning
confidence: 85%